2018
DOI: 10.1007/s00382-018-4085-7
|View full text |Cite
|
Sign up to set email alerts
|

On the role of horizontal resolution over the Tibetan Plateau in the REMO regional climate model

Abstract: A number of studies have shown that added value is obtained by increasing the horizontal resolution of a regional climate model to capture additional fine-scale weather processes. However, the mechanisms leading to this added value are different over areas with complicated orographic features, such as the Tibetan Plateau (TP). To determine the role that horizontal resolution plays over the TP, a detailed comparison was made between the results from the REMO regional climate model at resolutions of 25 and 50 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 50 publications
(74 reference statements)
1
31
0
Order By: Relevance
“…Following the CORDEX experiment design, REMO has been successfully used for long-term climate simulations over multiple domains, such as Europe, Africa, Asia, America, and the Mediterranean (Jacob et al 2012;Remedio et al 2019). The REMO model (version 2015) simulates most climate types relatively well, with a low bias and a high skill score (Remedio et al 2019;Xu et al 2018) have shown that REMO (REMO2015), driven by ERA-Interim reanalysis data, can reliably simulate climate over the Tibetan Plateau. We selected REMO simulations available from the CORDEX experiment for the East Asia domain (Fig.…”
Section: Regional Climate Model Remo and Experiments Designmentioning
confidence: 99%
“…Following the CORDEX experiment design, REMO has been successfully used for long-term climate simulations over multiple domains, such as Europe, Africa, Asia, America, and the Mediterranean (Jacob et al 2012;Remedio et al 2019). The REMO model (version 2015) simulates most climate types relatively well, with a low bias and a high skill score (Remedio et al 2019;Xu et al 2018) have shown that REMO (REMO2015), driven by ERA-Interim reanalysis data, can reliably simulate climate over the Tibetan Plateau. We selected REMO simulations available from the CORDEX experiment for the East Asia domain (Fig.…”
Section: Regional Climate Model Remo and Experiments Designmentioning
confidence: 99%
“…In general terms, most of the added value of regional models over land areas in comparison to global coupled models (GCM) simulations can be traced back to a better representation of the orography (e. g. Di Luca et al 2015;Xu et al 2018;Teichmann et al 2013). However, coupled regional models show a clear improvement with respect to both uncoupled atmospheric simulation and the driving global model in regions of intense air-sea interactions or of large-scale feedback (e.g., Cabos et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main sources of total PW transport over eastern China is the southwesterly winds from the Bay of Bengal (Xu et al, 2019b). In positive TIOD years ( Figure 5), the TIOD has a positive connection with the amount of water vapor transported to China via the Bay of Bengal (Guan and Yamagata, 2003;Xu et al, 2019a). When the TIOD is in its positive phase, the total PW FIGURE 1 | The first leading SVD modes for (A) the rice yield anomaly pattern, (B) the TIOD-like SST pattern, and (C) the expanded time coefficients.…”
Section: Possible Mechanism Of Impact Of the Tiod-like Sst With The Pmentioning
confidence: 99%